THE EFFECTIVENESS OF E-JOBSHEET USING FLIP PDF PROFESSIONAL APPLICATION IN THE COURSE OF ROAD PAVEMENT CONSTRUCTION - Ismon, Asrizal; Putri, Prima Yane (Teknik Sipil Universitas Negeri Padang, 2023)
The constraint in the course